Regulación constitucional de la participación de los trabajadores en la economía y en la empresa - Colomer Viadel, Antonio (Revista de Derecho Político, 2017)
Resumen: En el texto de la Constitución española de 1978, se opta por un modelo participativo, que se refleja en los artículos 7 y 9, en el título VII (Economía y Hacienda) y, en particular, el artículo 129 que parece contener un programa revolucionario en relación con la economía y la empresa y el acceso de los trabajadores a la propiedad. Sin embargo, no ha existido la voluntad política de desarrollar toda la potencialidad de la Constitución. Incluso se ha disminuido la tendencia participativa, especialmente en el campo social y económico. Summary: Preliminary note. 1. Introduction. 2. The economic constitution. A. Participation in Social Security and other bodies on quality of life and overall well-being. B. Participation in the company and its community dimension. C. Cooperatives. D. The access of workers to the ownership of the means of production. The participation economy and the Social and solidarity economy. Abstract: The Spanish Constitution of 1978 opt for a participatory model, which is reflected in articles 7 and 9, in title VII (Economy and Finance) and, in particular, article 129 which seems to contain a revolutionary programme for the Economy and the companies, and the workers access to the property. However, there has been no political will to develop the full potential of the Constitution. Even declined the participatory trend, especially in the social and economic field.